My Atlas. - Flusser, Vilém (Flusser Studies, 2015)
A reprint of the article "My Atlas," by Vilém Flusser about the different types of atlas including historical atlas, encyclopaedic atlas and geographical atlas which appeared in the May 2012 edition of the electronic journal is presented.